An application study case tradeoff between throughput and latency on fog-cloud cooperation. (7th May 2020) - Dantas, Mario A.R.; Bogoni, Paulo Eduardo; Filho, Paulo José De Freitas
Nowadays, several research works are targeting fog-cloud environments cooperation in the organisations. Examples of well-known challenges are workload offloading, shared services, power consumption, security and communication delays. The communication subject is an essential metric to be observed in this cooperation. Bandwidth, throughput and latency are important parameters that affect the fog-cloud cooperation and are frequently misunderstood. In this paper, it is presented a research work, in which we took in consideration a real information system (IS) application which could execute under a cooperation of a fog-cloud configuration. Therefore, we conceived a case study to investigate specially the tradeoff between the throughput and latency parameters and provide more accurate idea of an application requirements in a fog-cloud cooperation scenario.